RELIABILITY-BASED APPROACH FOR RESIDUAL LIFE PREDICTION OF BRIDGES SUBJECTED TO EARTHQUAKE SHOCKS DEGRADATION - Maizuar Maizuar; said jalalul akbar; Wesli Wesli (UNIVERSITAS MALIKUSSALEH, 2019)
Structural degradation caused by sudden damaging extreme events (e.g. earthquake) has significant impact on residual life of bridges and ultimately the collapse of bridges. This paper presents a reliability-based approach of a bridge subjected to shock degradation caused by earthquake events. In particular, this study develops a numerical procedure for assessing time dependent probability of failure to estimate the residual life a bridge. Key factors that govern the residual life of a bridge (e.g., damage size caused by earthquake shocks and loss of initial structural capacity) were investigated. The results of study show that both damage size caused by earthquake shocks and loss of initial structural capacity are key factors that govern residual life of a bridge. Keywords: residual life, earthquake, shock degradation, bridge.